The opposite house : a novel - Oyeyemi, Helen (Anchor Books, 2008)
Maja, daughter of a black Cuban couple, was only five years old when the family emigrated to London. Growing up, she speaks Spanish and English, but longs for a connection to her African roots. Now in her early twenties, Maja is haunted by the desire to make sense of the threads of her history; meanwhile, her mother has found comfort in Santería--a faith that melds Catholic saints and the Yoruba gods of West African religion. Maja's narrative is one of two parallel voices in this novel. Yemaya Saramagua speaks from the other side of the reality wall--in the Somewherehouse, which has two doors, one opening to London, the other to Lagos. A Yoruban goddess, Yemaya is troubled by the ease with which her fellow gods have disguised themselves as saints and reappeared under different names and faces. As Maja and Yemaya move closer to understanding themselves, they realize that the journey to discovering where home truly lies is at once painful and exhilarating.--From publisher description.